Avoidable severe morbidity from wound dehiscence after cesarean section: Practice and experience from a tertiary referral hospital in a low-income setting, Tanzania—a mixed-methods study - Mgaya, Andrew Hans; Samuel, Raymond Oyugi; Mhando, Isaya Erasto; Kimwela, Hery Omary; Mgaya, Hans Nathanael (Frontiers in Surgery, 2025)
IntroductionThis study aims to determine care-related risk factors and explore the perspectives of women and care providers about complete wound dehiscence after cesarean section at a tertiary referral and university hospital.MethodsA mixed-methods study was conducted at Muhimbili National Hospital in Dar es Salaam between April 2019 and December 2020. A case control survey compared the characteristics of interest of 131 cases of complete wound dehiscence with 393 randomly selected controls comprising cesarean deliveries between January 2015 and December 2020. In addition, six semistructured individual in-depth interviews with women, one focus group discussion with care providers, and unstructured direct observations were performed between July 2020 and December 2020. Pearson's Chi-square test and Fisher's exact test were used to determine the percentage difference of risk factors of complete wound dehiscence between cases and controls. Thereafter, a multivariate regression analysis determined the role of the independent risk factors. A thematic analysis was used to describe qualitative data.ResultsOut of 524 women (131 cases and 393 controls), 75% of deliveries were performed by obstetric registrars and residents. Cases of complete wound dehiscence were more likely from cesarean deliveries performed by junior residents [odds ratio (OR) 1.8, 95% confidence interval (CI) 1.7–5.4]. Wound failure was characterized by complete wound dehiscence with intact sutures (70%) on loosely binding wound margins (62%) or avulsed from the fascial layers (38%). The perspectives of women and care providers were categorized into four themes: wound dehiscence as an indicator of the quality of care; effectiveness of clinical skill transfer and team work; maternal fear, stress, and socioeconomic burden; and significant external factors influencing care.ConclusionComplete wound dehiscence after cesarean section was highly associated with a suboptimal surgical technique, an ineffective structure and process of clinical skill transfer, and negative experience of care from patients and their families. The identified serious and preventable gaps in the quality of cesarean section stemmed from modifiable clinical and educational practices.